2016
DOI: 10.1016/j.cmi.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Functional balance between neuraminidase and haemagglutinin in influenza viruses

Abstract: Seasonal influenza A and B viruses are important human pathogens responsible for significant morbidity and mortality worldwide. In addition, influenza A zoonotic viruses are a constant pandemic threat. These viruses present two major surface glycoproteins: the haemagglutinin (HA) and the neuraminidase (NA). These two glycoproteins both recognize the sialic acid and have complementary activities, the HA binds the sialic acid through its receptor-binding site, the NA is a receptor-destroying enzyme that cleaves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 62 publications
3
108
0
Order By: Relevance
“…When, measured, the IC50 values were mostly reduced inhibition, and some were normal inhibition, due to mixed genotypes (H275 & 275Y) and the use of the chemiluminescent assay. The resistant Brisbane H1N1 that emerged in 2008 was supposed to be related to structural changes in the backbone of the NA that facilitated (imposed) the introduction of 275Y in the NA pocket to maintain both virus fitness and HA‐NA balanced activities 11, 25. In our study, the frequency of detection of resistance due to a 275Y substitution gradually increased during the surveillance, but the limited number of cases makes any interpretation difficult.…”
Section: Discussionmentioning
confidence: 72%
“…When, measured, the IC50 values were mostly reduced inhibition, and some were normal inhibition, due to mixed genotypes (H275 & 275Y) and the use of the chemiluminescent assay. The resistant Brisbane H1N1 that emerged in 2008 was supposed to be related to structural changes in the backbone of the NA that facilitated (imposed) the introduction of 275Y in the NA pocket to maintain both virus fitness and HA‐NA balanced activities 11, 25. In our study, the frequency of detection of resistance due to a 275Y substitution gradually increased during the surveillance, but the limited number of cases makes any interpretation difficult.…”
Section: Discussionmentioning
confidence: 72%
“…NA inhibitors such as oseltamivir (Tamiflu), zanamivir (Relenza) and peramivir (Rapivab) have been developed to treat influenza infections (Burnham et al 2013). Studies of drug-resistant influenza strains have demonstrated that a balance between the contrasting activities of HA and NA dictates viral growth, transmission and host adaptation (Baigent and McCauley 2001;Gaymard et al 2016b). For example, oseltamivirresistant strains isolated after 2007 exhibited a particular mutation in NA, which coexisted with a new variant of HA, leading to a virus with better "viral fitness" likely due to a readjusted HA-NA balance (Gaymard et al 2016a;Rameix-Welti et al 2008).…”
Section: Influenza Na's Ability To Cleave Sia On Host Cell Glycoconjumentioning
confidence: 99%
“…Neuraminidase works in conjunction with the HA receptor of the influenza virus to infect and spread virus effectively [35, 36]. As such, studying the NA and HA proteins together is crucial to understanding viral evolution.…”
Section: Discussionmentioning
confidence: 99%